INGO Performance Management Practices and the Need for Accountability - Conlin, Brad (Université d'Ottawa / University of Ottawa, 2015)
This study provides a comprehensive look at the current state of best practices in performance appraisal systems in the public and private sector. From this, the main objective for this research paper is to investigate the reasons why INGOs are not currently able to properly implement a ‘best practices’ based performance appraisal system. Furthermore, this paper will provide both future research questions, as well as practitioner based recommendations. In addition, it will examine the need for higher levels of accountability in INGOs through appropriate performance appraisal systems.
Keywords: Human Resources; Performance Appraisals; Performance Management; Accountability; INGO; NGO; International Human Resources; Accountability; International; Sources of Appraisal; Appraisal Frequency; Developmental; Appraisal